Penataan Kembali Pusat Kota: Suatu Analisis Proses - Danisworo, Mohammad (Center for Research and Community Services ITB, 1996)
Land is an urban resource whose existence is becoming critical due to its non-renewable nature while the pressure for its utilization keeps increasing. Through the process of recycling, the land carrying capacity could be increased and the revitalization of the city center can he realized.